Thirty years with cervical vestibular myogenic potentials: a critical review on its origin - Kjærsgaard, Jonas Bruun; Hougaard, Dan Dupont; Kingma, Herman (Frontiers in Neurology, 2025)
Myogenic potentials generated by acoustic stimulation of the vestibular system have been reported since 1964. This examination became better known as cervical vestibular evoked myogenic potentials (cVEMPs) and gained increasing clinical application since the nineties. Since its discovery, the saccule has been conceived as the most likely vestibular end-organ driving these myogenic potentials of the neck. As findings from both animal and human studies for a long time uniformly provided evidence supporting this theory, cVEMP assessment has become synonymous with evaluation of saccular and inferior vestibular nerve function. This review of the basic evidence supporting this conclusion, questions if cVEMP may be considered as being predominantly or even exclusively driven by the activation of any single vestibular end-organ. We conclude that the results of this review show that contributions from the crista ampullaris of all three ipsilateral semicircular canals, as well as the ipsilateral utricle cannot be ruled out in clinically conducted cVEMP assessments.